Short‐term tetrabromobisphenol A exposure promotes fibrosis of human uterine fibroid cells in a 3D culture system through TGF‐beta signaling. Issue 2 (15th January 2022) - Liu, Jingli; Yu, Linda; Castro, Lysandra; Yan, Yitang; Clayton, Natasha P.; Bushel, Pierre; Flagler, Norris D.; Scappini, Erica; Dixon, Darlene
Abstract: Tetrabromobisphenol A (TBBPA), a derivative of BPA, is a ubiquitous environmental contaminant with weak estrogenic properties. In women, uterine fibroids are highly prevalent estrogen‐responsive tumors often with excessive accumulation of extracellular matrix (ECM) and may be the target of environmental estrogens. We have found that BPA has profibrotic effects in vitro, in addition to previous reports of the in vivo fibrotic effects of BPA in mouse uterus. However, the role of TBBPA in fibrosis is unclear. To investigate the effects of TBBPA on uterine fibrosis, we developed a 3D human uterine leiomyoma (ht‐UtLM) spheroid culture model. Cell proliferation was evaluated in 3D ht‐UtLM spheroids following TBBPA (10 −6 –200 µM) administration at 48 h. Fibrosis was assessed using a Masson's Trichrome stain and light microscopy at 7 days of TBBPA (10 −3 µM) treatment. Differential expression of ECM and fibrosis genes were determined using RT² Profiler™ PCR arrays. Network and pathway analyses were conducted using Ingenuity Pathway Analysis. The activation of pathway proteins was analyzed by a transforming growth factor‐beta (TGFB) protein array. We found that TBBPA increased cell proliferation and promoted fibrosis in 3D ht‐UtLM spheroids with increased deposition of collagens. TBBPA upregulated the expression of profibrotic genes and corresponding proteins associated with the TGFB pathway. TBBPA activated TGFB signaling through phosphorylation of TGFBR1 and downstream effectors—small mothers against decapentaplegic ‐2 and ‐3 proteins (SMAD2 and SMAD3). The 3D ht‐UtLM spheroid model is an effective system for studying environmental agents on human uterine fibrosis. TBBPA can promote fibrosis in uterine fibroid through TGFB/SMAD signaling.